2012
DOI: 10.26719/2012.18.9.985
|View full text |Cite
|
Sign up to set email alerts
|

Oral and pharyngeal cancers in Yemen: a retrospective study

Abstract: Hospital-based studies have revealed very high relative frequencies of oral and pharyngeal cancers in Yemen. This study estimated the relative frequencies of oral and pharyngeal cancers among Yemeni cancer patients registered in 2007 and 2008 and determined patients' demographic and tumour characteristics. Of the registered 7515 cases, 302 (4.0%) were oral cancer and 239 (3.2%) pharyngeal cancer. Oral cancer was significantly more frequent among females while pharyngeal cancer was significantly more frequent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…Two researches conducted in Yemen which share the border with Jazan showed higher number of females suffering from oral cancer when compared to males (Sawair et al, 2007;Halboub et al, 2012). This probably justifies the almost equal percentage of male and female oral cancer cases obtained in the current study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Two researches conducted in Yemen which share the border with Jazan showed higher number of females suffering from oral cancer when compared to males (Sawair et al, 2007;Halboub et al, 2012). This probably justifies the almost equal percentage of male and female oral cancer cases obtained in the current study.…”
Section: Discussionsupporting
confidence: 60%
“…Residents as young as 10-13 years of age have been reported to be indulged in the habit of shamma dipping. The appropriate percentage of the users could be much higher as the use of shamma is illegal in the country and there are chances of false reporting by the users (Salem et al, 1984;Allard et al, 1999;Halboub et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…of Yemeni adults (n=2500), no oral cancers were reported . A 2012 large‐scaled, retrospective study evaluating the frequency of oral and pharyngeal cancers among Yemeni cancer patients registered in 2007 and 2008 (n=7515) found that 541 (7.2%) had primary malignancies of oral and pharyngeal tissues, of which the tongue was the most affected oral site (53.6%), and women were the most affected . Interestingly, most of the reported oral cancer cases were referred from the Al‐Hodeida and Hajja governorates (west of Yemen), where smokeless tobacco use and water pipe smoking are very common.…”
Section: Oral Manifestations Of Khat Usagementioning
confidence: 99%
“…In Yemen, a recent study revealed a quite high relative frequency of oral cancer among Yemenis, 3.7%, when compared to the neighboring countries. Besides, the majority of cases were detected at advanced stages (Halboub et al, 2012).…”
Section: Introductionmentioning
confidence: 99%